2022
DOI: 10.3390/ma15041356
|View full text |Cite
|
Sign up to set email alerts
|

Electrical and Thermal Properties of Carbon Nanotube Polymer Composites with Various Aspect Ratios

Abstract: In response to the rising need for flexible and lightweight materials capable of efficient heat transport, many studies have been conducted to improve the thermal properties of polymers via nanofillers. Among the various nanofillers, carbon nanotubes (CNTs) are considered as the most promising, owing to their excellent thermal and electrical properties. Accordingly, CNT/polymer composites can be used as flexible and lightweight heat transfer materials, owing to their low density. In this study, we fabricated m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
28
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 42 publications
1
28
0
Order By: Relevance
“…Carbon materials (such as carbon nanotubes (CNTs)), metal materials (such as copper (Cu)), semiconductor material (such as gallium nitride (GaN)) and polymer materials (such as polylactic acid (PLA)) have become the most favourable selection for preparing nanofluids [10]. Among them, CNTs nanofluids are considered as the best nanofluids as they are having the highest thermal conductivity compare to other nanoparticles [11][12]. Jiang et al, [13] suggested that CNTs became one of the effective materials providing higher thermal conductivity of nanofluids compared to other nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Carbon materials (such as carbon nanotubes (CNTs)), metal materials (such as copper (Cu)), semiconductor material (such as gallium nitride (GaN)) and polymer materials (such as polylactic acid (PLA)) have become the most favourable selection for preparing nanofluids [10]. Among them, CNTs nanofluids are considered as the best nanofluids as they are having the highest thermal conductivity compare to other nanoparticles [11][12]. Jiang et al, [13] suggested that CNTs became one of the effective materials providing higher thermal conductivity of nanofluids compared to other nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…CNTs consist of carbon nanoparticles with common range in diameter from 0.5nm to 1.5nm and above 100nm for single-walled carbon nanotubes (SWCNTs) and multi-walled carbon nanotubes (MWCNTs), respectively. Basically, CNTs are constructed and rolled into a cylindrical shape by using one-dimensional graphene structures [12]. To produce CNTs nanofluids, CNTs are immersed in a base fluid such as water, oil and ethylene glycol.…”
Section: Introductionmentioning
confidence: 99%
“…25,26 Among all conductive networks, CNTs are considered to be fillers for composite formation because of their stability due to the sp 2 covalent bond. 27,28 Distinctly, multiwalled CNTs (MWCNTs) possess a promising conductive framework as well as act as a reducing agent (for V 5+ to V 3+ ) which provides a high surface area, excellent electrical and thermal conductivities, and also mechanical properties to form a functional composite with NVP. 29 In spite of this, incorporation of MWCNT reduces polarization by ensuring intimate contact between nanotubes and NVP particles for fast Na-ion transport.…”
Section: Introductionmentioning
confidence: 99%
“…The conductivity of the material is one of the critical factors impacting its electrochemical performance. Currently, incorporating electrically conductive additives such as porous carbon, graphene, carbon nanotubes (CNTs), and so forth into the NVP matrix or making hybrid with it not only provides a large electrode/electrolyte contact area but also inhibits the overgrowth of particles which ultimately improves the electrochemical performance. , Among all conductive networks, CNTs are considered to be fillers for composite formation because of their stability due to the sp 2 covalent bond. , Distinctly, multiwalled CNTs (MWCNTs) possess a promising conductive framework as well as act as a reducing agent (for V 5+ to V 3+ ) which provides a high surface area, excellent electrical and thermal conductivities, and also mechanical properties to form a functional composite with NVP . In spite of this, incorporation of MWCNT reduces polarization by ensuring intimate contact between nanotubes and NVP particles for fast Na-ion transport. , It also accommodates volume change accompanied due to intercalation/de-intercalation of Na + ions.…”
Section: Introductionmentioning
confidence: 99%
“…The scientific community has been captivated by the development of novel conductive polymer composite materials (CPCs) with specified and fundamentally new properties as a result of the addition of nanometer-scale components. [1][2][3] The inherently insulating polymers are cheaper in comparison to electrically conductive polymers. Conductive polymers have wide application areas such as electronics and energy storage devices, corrosion inhibitors, pollutant degradation, electromagnetic interference shielding materials, and sensors.…”
Section: Introductionmentioning
confidence: 99%